THU0251 How to PREDICT That Early Arthritis without Rheumatoid Factor and ACPA May Develop into Rheumatoid Arthritis According to Acr/Eular 2010 after A 3-Years Follow-Up? Results from the ESPOIR Cohort. (10th June 2014) - Mouterde, G.; Lukas, C.; Rincheval, N.; Saraux, A.; Dieudé, P.; Combe, B.
Abstract : Objectives: To describe disease course of patients without rheumatoid factor (RF) and anti-citrullinated protein auto-antibodies (ACPA) in an inception cohort of early arthritis patients. To determine baseline predictors of fulfilling 2010 ACR/EULAR criteria for rheumatoid arthritis (RA) at 3 years in these patients Methods: Patients presenting with synovitis of at least 2 joints for 6 weeks to 6 months were included in the multicenter French ESPOIR cohort. Following data were collected at baseline for those who were negative for IgM RF and ACPA (anti-CCP2): clinical and biological features of arthritis, HLA-DRB1* typing, socio economic factors, comorbidities, radiographs of hands, wrists, and feet (modified Sharp score). RA was defined according to the 2010 ACR/EULAR classification criteria (1) at any visit during the first 3 years of follow-up or by typical RA erosion (2). Alternative diagnoses were reported among patients who did not fulfill ACR/EULAR criteria. Logistic regression was performed to evaluate the association between RA diagnosis at 3 years and baseline variables. Results: Of the 813 recruited patients, 406 (49.9%) were negative for both RF and anti-CCP2. They had the following features: age 49±13 years, females 77%, mean disease duration: 102±50 days, DAS28 4.95±1.3, HAQ score 0.93±0.68, CRP 18.6±34.2 mg/l; 57 (14.1%) had antinuclear antibodies (ANA) and 39 (9.6%) were RF-IgA positive. 246/387 patients (63.6%) fulfilled ACR/EULAR 2010 criteria for RA at baseline (56.3% had a score ≥6 and 19.8% had typical RA erosion) and 269/374 (71.9%) at 3 years. In this seronegative cohort, diagnosis of RA at 3 years was associated with the following initial factors: symmetric involvement (OR=3 [1.41; 6.39], p=0.004), morning stiffness (>median: 45 min) (OR=2.48 [1.34; 4.57], p=0.004), pain at rest on a VAS (>median: 34/100) (OR=2.14 [1.14; 4.01], p=0.017), number of tender joints (>median: 6) (OR=3.51 [1.78; 6.92], p<0.001) and presence of feet erosions (OR=2.96 [1.19; 7.40], p=0.020). Presence of ANA (OR=0.38 [0.17; 0.87], p=0.021), transaminases elevation (OR=0.52 [0.28; 0.94], p=0.032) and living in the south of France (OR=0.45 [0.22; 0.90], p=0.024) may contribue in protecting the patient from developping RA. No association between extra-articular manifestations, HLA-DR3 and "seronegative RA" was observed. Among the 105 patients who did not fulfill ACR/EULAR 2010 criteria for RA at 3 years, 44 had another definite diagnosis: psoriatic arthritis (n=10), spondyloarthritis (n=7), erosive hand osteoarthritis (n=5), connective tissue disease and vasculitis (n=8), polymyalgia rheumatica or RS3PE syndrome (n=3). Conclusions: Patients with early arthritis and without RF and ACPA are more liable to have RA at 3 years if they have typical inflammatory characteristic of pain, symmetric involvement of numerous joints and feet erosions. Detection of ANA and transaminases elevation should suggest non RA diagnosis. References: Aletaha D, Neogi T, Silman AJ, et al. Ann Rheum Dis. 2010;69(9):1580-8. van der Heijde D, van der Helm-van Mil AH, Aletaha D, et al. Ann Rheum Dis. 2013 Apr;72(4):479-81. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.5524